Zoo Visitors' Affective Responses to Observing Animal Behaviors. Issue 1 (2nd January 2016) - Luebke, Jerry F.; Watters, Jason V.; Packer, Jan; Miller, Lance J.; Powell, David M.
ABSTRACT: The opportunity to observe or interact with animals in a zoo is often vital in influencing visitors' positive feelings towards animals and ultimately their conservation behavior. This study explores the relationship between observed animal behavior and zoo visitors' responses. A self-administered questionnaire was completed by 717 visitors across four exhibits (giraffe, lion, cheetah, and red panda) at three zoos (Brookfield Zoo, San Diego Zoo Safari Park, and Central Park Zoo). The questionnaire measured observed animal behaviors and visitors' predispositions, affective responses, and meaning-making at animal exhibits. Multivariate path analyses indicated that up-close encounters with zoo animals, along with observable active animal behaviors, predicted visitors' reported positive affective responses which, in turn, predicted their meaning-making. These findings lend support to the role of positive affect as a mediator between observable animal behaviors and visitor meaning-making. Implications are discussed in relation to achieving both conservation education and animal welfare outcomes.